Anti-inflammatory potential of SGLT2 inhibitors: a systematic review and meta-analysis of preclinical studies in rodents. (3rd October 2022) - Theofilis, P; Sagris, M; Oikonomou, E; Antonopoulos, A S; Siasos, G; Tsioufis, K; Tousoulis, D
Abstract: Background: Sodium-glucose cotransporter-2 (SGLT2) inhibition is at the forefront of scientific research due to their astonishing effect in ameliorating the prognosis of cardiorenal diseases. Several mechanisms have been proposed for these pleiotropic effects, including anti-inflammatory ones. Purpose: Our systematic review and meta-analysis aimed to assess the effect of SGLT2 inhibitors on inflammatory markers in experimental rodent models. Methods: We conducted a literature search to detect studies examining the effect of SGLT2 inhibitors on inflammatory markers [interleukin-6 (IL-6), C reactive protein (CRP), tumor necrosis factor-α (TNF-α), and monocyte chemoattractant protein-1 (MCP1)] in rodent animal models. Consequently, a meta-analysis of the included studies was performed, assessing the differences in the levels of the inflammatory markers between the treatment and the control group as its primary outcome. Studies not reporting in vivo experiments on mice/rats or not measuring inflammatory markers in the plasma or serum were excluded. Moreover, studies not administering SGLT2 inhibitors as treatment or simultaneously utilizing SGLT2 inhibitors with other treatment were further excluded. Effect sizes were pooled via random-effect model and results are expressed as standardized mean difference (SMD) with 95% confidence intervals (CIs). Correction for small-sample bias was also applied with the use of Hedge's g. I 2 was chosen as the measure of between-studies heterogeneity. Results: The systematic literature review yielded 30 studies whose meta-analysis suggested that treatment with an SGLT2 inhibitor resulted in decreases of IL-6 [standardized mean difference (SMD): −1.49, 95% CI −2.00 to −0.99, I 2 : 71%), CRP (SMD: −2.17, 95% CI −2.80 to −1.53, I 2 : 64%), TNF-α (SMD: −1.68, 95% CI −2.05 to −1.31, I 2 : 38%), and MCP1 (SMD: −2.04, 95% CI −2.91 to −1.17, I 2 : 66%) (Figure 1). The effect was of lesser magnitude in cases of empagliflozin use (p for interaction=0.03 to 0.05). Possible publication bias was noted in the case of IL-6 and CRP. The findings remained largely unaffected after the sensitivity analyses and the exclusion of outlying studies. Conclusion: The present meta-analysis suggests that SGLT2 inhibition results in reduction of inflammatory markers in rodents, suggesting an anti-inflammatory mechanism of action Funding Acknowledgement: Type of funding sources: None.